Bulletproof barista - Coyle, Cleo (Coyle, Cleo. Coffeehouse mystery, 2023)
"Only Murders in Gotham, the smash hit streaming show, is famous for filming in authentic New York City locations and using real New Yorkers as extras. For their latest episode, they've chosen to spotlight the century-old Village Blend and its quirky crew of baristas. But when the film crew's week of shooting delivers an actual shooting, Clare Cosi and her staff find themselves at the scene of a true crime"--